Hyaluronic acid‐g‐lipoic acid granular gel for promoting diabetic wound healing - Shixi Zhang; Yuqing Pan; Zhiyuan Mao; Jiahui Zhang; Kunxi Zhang; Jingbo Yin; Chen Wang (Bioengineering & Translational Medicine, 2023)
Abstract Diabetic patients are prone to developing chronic inflammation after trauma and have persistent nonhealing wounds. Reactive oxygen species (ROS) and recurrent bacterial infections at the site of long‐term wounds also further delay skin wound healing and tissue regeneration. In this study, a granular gel (which exhibits ROS scavenging and antibacterial properties) is fabricated based on hyaluronic acid‐g‐lipoic acid (HA‐LA). Briefly, HA‐LA is synthesized to fabricate HA‐LA microgels, which are further assembled by Ag+ via its coordination effect with disulfide in dithiolane to form a granular gel. The extrudable bulk granular gel possesses a shear‐thinning feature and is immediately restored to a solid state after extrusion, and this can be easily applied to the whole wound area. Therefore, the grafted LA not only allows for the construction of the granular gel but also removes excess ROS from the microenvironment. Additionally, the presence of Ag+ realizes the assembly of microgels and has antibacterial effects. In vivo experiments show that the HA‐LA granular gel eliminates excessive ROS at the wound site and up‐regulates the secretion of reparative growth factors, thus, accelerating common and diabetic wound healing significantly. Therefore, the ROS‐scavenging granular gel that can be applied to the wound surface with chronic inflammation demonstrates strong clinical utility.